Sherrie : Behind the Laughter - Hewson, Sherrie, 1950- (London Harper, 2011)
Join Loose Women's Sherrie Hewson on her rollercoaster ride through the laughter, tears and tantrums of an extraordinary life lived on and off the screen. Sherrie Hewson is one of Britain's best loved telly stars.
Include Illustrations
Biography
Keywords: Television actors and actresses